AUTHOR ATTRIBUTION IN SUICIDE NOTES: EVIDENCE FROM APPLIED LINGUISTICS - BASIM, Yahya Jasim (Comparative Legilinguistics, 2012)
Authorship attribution is a branch of authorship identification whose aim is to examine the characteristic features of a piece of writing to establish its author. The present study applies the methods and techniques of forensic and applied linguistics to the analysis of a suicide note believed to have been written by a 49-year old brigadier in the Iraqi Army who was found shot in the head. The accident was regarded as a suicidal act, which the family of the deceased challenged. They suspected an assassination disguised as a suicide and claimed that the suicide note left close to the deceased was either a mere fabrication, or was written under duress. The present study attempts to verify these assumptions using the techniques commonly followed in authorship attribution in analyzing the form and content of the suicide note and comparing it to a text that is known to have been written by the deceased. The results indicate that the suicide note was not simulated or tampered with and was not written under threat or duress.